КОМП’ЮТЕРНА СИСТЕМА МОДЕЛЮВАННЯ ПРОЦЕСІВ ЦІНОУТВОРЕННЯ НА ОПТОВОМУ РИНКУ ЕЛЕКТРОЕНЕРГІЇ - Євдокімов, В.А.; Борукаєв, З.X.; Остапченко, К.Б. (Інститут електродинаміки НАН України, Київ, 2024)
The large-scale introduction into traditional energy systems of generating facilities and equipment that use renewable energy sources as part of the implementation of the energy decarbonization strategy leads to a change in the structure of electricity production and consumption, a rapid increase in the number of participants in trade and economic relations on the electricity market. This determines the need for conducting research in the direction of creating easy-to-use, functional object-oriented computer systems for modeling competitive market processes in terms of pricing management in order to increase the productivity and effectiveness of decisions made by market participants. The article formulates the principles, functionality and requirements for building such a class of computer modeling systems. Based on their application, the approximate composition of the functional modules of the computer system for modeling pricing processes with a single unified environment of information resources and computer models is determined. A deterministic algorithmic model is presented for the analysis of the dynamics of the volume distribution of electricity purchase and sale (demand) in the wholesale market segments as part of the computer models environment of the computer simulation system of price formation processes. The results of model calculations are presented for assessing the dynamics of demand in market segments, which are obtained using information resources and data presentation and visualization modules of the constructed computer simulation system. References 22, figures 2, table 1.